Prevalence of Needlestick Injuries and the preventive response of affected Dental healthcare persons working in Islamabad, Rawalpindi, and Abbottabad Pakistan. - Muhammad Umair; Abdul Manan; Sadia Rashid; Abdul Qadir; Nusrat Tariq; Akif Mahmud (Journal of University Medical & Dental College)
BACKGROUND AND OBJECTIVES: Needle sticks and other sharps injuries are common and serious hazards in healthcare facilities, exposing healthcare workers to blood-borne pathogens like HIV, hepatitis B, and C and affecting the physical and psychological health of dental staff. Our study aims to find the prevalence of needle injuries and preventive responses by affected ones.